Short Communication: The diversity of epipelic diatoms as an indicator of shrimp pond environmental quality in Lampung Province, Indonesia - SUPONO SUPONO; SITI HUDAIDAH (Biodiversitas Journal of Biological Diversity, 2018)
Supono, Hudaidah S. 2018. Short Communication: The diversity of epipelic diatoms as an indicator of shrimp pond environmental quality in Lampung Province, Indonesia. Biodiversitas 19: 1220-1226. Epipelic diatoms live by attaching to sediment. Their existence is strongly affected by water and sediment quality. The purpose of this research was to analyze the structure of epipelic diatom populations on the bottom of shrimp ponds and to determine the correlation between epipelic diatom diversity and the quality of water and of pond bottom sediment. This exploratory research was conducted on twelve shrimp ponds during the water preparation period (pre-stocking). Data were collected to analyze the correlation between water and sediment qualities. The results showed that Nitzschia and Pleurosigma were the dominant epipelic diatoms in the shrimp ponds. Epipelic diatom diversity in shrimp ponds was affected by water quality parameters (namely total alkalinity, organic matter and nitrate) as well as sediment quality parameters (namely cation exchange capacity, clay content and organic matter content).